2nd National REDi Congress 2023 Book of Abstracts - REDi Romblon State University (Romblon State University Research Journal, 2023)
In the context of the "new normal," where virtual gatherings have become the norm, the theme also emphasizes the adaptability and resilience of HEIs in coping with the challenges brought about by unprecedented circumstances. By embracing technological advancements and virtual platforms, 2nd REDi National Congress ensures that knowledge exchange and capability building continue unhindered. The chosen theme aims to encapsulate the essence of the REDI Congress organized by the RSU-REDi unit. It emphasizes the pivotal role of Higher Education Institutions (HEIs) as "nebulae of innovations" where research and development (R&D) activities flourish, creating a galaxy of new ideas and discoveries. These innovations are confined within the academic realm and extended through extension activities catering to marginalized and underserved sectors. Furthermore, the theme highlights the all-encompassing nature of the congress, where all papers produced by faculty, staff, and students are considered for presentation. Regardless of whether the research is externally, institutionally, or privately funded, initiated by individuals themselves, or stems from academic pursuits like theses, dissertations, and term papers, each contribution holds equal value in advancing the frontiers of knowledge. Overall, the theme "Navigating the Frontiers of Innovation: Fostering Sustainable Development and Inclusivity in Higher Education Institutions (HEIs)" aims to motivate, inspire, and unite stakeholders within HEIs in their collective endeavor to create a brighter future through cutting-edge research, inclusive practices, and a commitment to sustainable development. The REDI Congress, which began in 2020, is an annual activity of the RSU-REDi unit in its commitment to highlight quality and high-impact R&D and extension outputs in the congress. Believing that a congress like this can help sustain the culture of sharing towards future-ready HEIs, it aims to virtually gather university faculty, teachers, graduate students, and experts for scholarly interactions, knowledge exchange, and capability building in the new normal. All papers completed by faculty, and staff, including externally funded research, institutionally funded projects, and privately funded initiatives, as well as theses, dissertations, term papers, and advisee’s theses/dissertations (with consent of primary researchers), are considered for presentation at the congress.